Can Devic Disease Involve Peripheral Nerves? - Ghosh, Jagabandhu; Ghosh, Joydeep (Journal of Pediatric Neurology, 2015)
Devic disease (DD) or neuromyelitis optica (NMO) is a rare demyelinating disease of central nervous system in children. It may have monophasic or relapsing course. A diagnosis of DD requires involvement of unilateral or bilateral optic nerves, more than three longitudinal segments of the spinal cord and presence of NMO-immunoglobulin G or antiaquaporin 4 antibody in the serum. It is usually associated with normal cranial magnetic resonance imaging during first episode of DD. Here, we report a case of DD with unusual association of peripheral nerve involvement of the axonal type.
Keywords: neuromyelitis optica; demyelination; peripheral nerve; Devic disease